Consciousness and Conscience: Feminism, Pragmatism, and the Potential for Radical Change - Clara Fischer (Studies in Social Justice, 2010)
Pragmatist philosopher John Dewey famously stated that man is a creature of habit, and not of reason or instinct. In this paper, I will assess Dewey's explication of the habituated self and the potential it holds for radical transformative processes. In particular, I will examine the process of coming to feminist consciousness and will show that a feminist-pragmatist reading of change can accommodate a view of the self as responsible agent. Following the elucidation of the changing self, I will appraise key pragmatist concepts of inquiry, such as doubt and self-reflexivity, with regard to their treatment of deep-seated internalizations of oppressive norms and the initiation of change. Ultimately, I will argue that a feminist-pragmatist understanding of transformation is conducive not only to the project of personal transformation, but also to social and political change more generally.